Bauran Produk dan Harga Diskon Terhadap Keputusan Penggunaan Jasa Salon Tanta di Pematangsiantar - Tarigan, Wico Jontarudi; Girsang, Rosita Manawari; Sinaga, Mahaitin H (Jurnal Pendidikan Ekonomi Undiksha, 2022)
This study aims to determine whether the product mix and discount prices for Tanta salons can influence customers' decisions to use salon services. The sample is 40 respondents who often go to Tanta Salon. This study uses a quantitative descriptive method. Validity test, reliability test, and test are analytical techniques used in this study. Heteroscedasticity Test, Multiple Linear Regression Analysis, Autocorrelation, Normality, Multicollinearity, and Coefficient of Determination. The results of this study show that the product mix and discount prices at Tanta Salon Pematangsiantar have a good and significant influence on decision making. Product mix variables and discounted prices can explain 43.7 percent of decision-making variables (adjusted R square number 0.437). Other factors outside the scope of this research model influence or explain the remaining 56.3%.